Short Communication In-Vitro Chemical Control of Aspergillus flavus Causing Seed Rot of Crops of Family Brassicaceae (Biological Sciences - PJSIR, 2006)
Aspergillus flavus was frequently isolated from seeds of four crops of family Brassicaceae at different frequen- cies: mustard (40%), rape (37%), turnip (18%) and radish (16%). Five fungicides namely, Dithane M-45, Derosal 60 WP, Trimiltox Forte, Baytan 10 DS and Vitavax 200 were tested to evaluate the efficacy of these fungicides for the control of• flavus. Amongst the five fungicides tested, Baytan 10 DS completely controlled the colony growth of the fungus at the dose 100 mg/100 ml potato dextrose agar medium (PDA). This was followed by Vitavax 200 at the dose 25 mg, Derosal 60 WP at the dose of 150 mg, Trimiltox Forte at the dose100 mg, and Dithane M-45 at the dose 250 mg per 100 ml PDA.